Treating adult children of alcoholics : a behavioral approach - Ruben, Douglas H. (Practical resources for the mental health professional., 2001)
Treating Adult Children of Alcoholics showcases the first collection of treatment chapters devoted entirely to a systematic behavioral analysis of drinking and nondrinking offspring of alcoholic families. The author identifies the functional and behavioral characteristics that make up the adult children of alcoholics (ACOA) syndrome. This compendium combines current innovations in behavioral medicine with multi-componential interventions shown effective with the variety of disorders evident in this patient population. This handbook for practitioners is richly laced with case examples and addresses the needs of therapists seeking fast, effective and proven treatments for longstanding clinical symptoms of children of alcoholics. Key Features * First book to use behavioral analysis to talk about Adult Children of Alcoholics * Gives introductory principles of conditioning in opening chapters for novice readers * First book to say ACOA patterns are predictable, measurable, and treatable in a short time * Gives scientifically based criteria to "rate your date" and prevent repeated relationship failures * Introduces a new assessment device to diagnose ACOAs * Warns therapists of recovery sabotage and how to overcome it